Talking to strangers : What we should know about the people we don't know - Gladwell, Malcolm, ....- (London : Allen Lane, 2019)
Through a series of encounters and misunderstandings - from history, psychology and infamous legal cases - Malcolm Gladwell takes us on an intellectual adventure into the darker side of human nature, where strangers are never simple and misreading them can have disastrous consequences.
Keywords: Sociale psychologie; communicatie